Southeast Asian Ecotheology Model: An Analysis of the Role of the Thai Sangha in Mitigating the Ecological Crisis - Paison Da-Oh (Al-Widad, 2026)
Ideally, the ecological crisis in Southeast Asia should be addressed through strong technocratic policies and scientific approaches. However, the reality shows that environmental mitigation efforts often remain ineffective due to the absence of ethical foundations and the erosion of spiritual awareness in the human–nature relationship. In this context, the Theravāda Buddhist tradition in Thailand offers an alternative approach through ecotheology, combining spirituality, ecological awareness, and social activism. This research aims to analyze the role of the Thai Sangha as a regional ecotheological model and evaluate its relevance for developing a Southeast Asian ecotheological framework. The study employs a qualitative library research method using content analysis and comparative review of academic literature, religious documents, and ecological monastic practices such as tree ordination, green monasteries, and community forest management. The findings reveal that the Thai Sangha has successfully transformed Buddhist spirituality into tangible ecological action, providing an effective response to environmental crises. Thailand’s ecotheology shows significant potential to be adopted regionally when institutionalized and implemented through cross-sectoral collaboration involving the state, local communities, and environmental NGOs. This study proposes a foundational academic framework for developing a Southeast Asian Ecotheology Model, based on local spirituality, ecological consciousness, and community participation as transformative strategies for mitigating ecological crises in the future.